Psychotic Features Abated with Vitamin D Treatment in a Patient with Major Depressive Disorder - David C. Fipps; Elisabet Rainey (Case Reports in Psychiatry)
Introduction. Vitamin D deficiency is common in psychiatric populations, and vitamin D has been used as an add-on medication in major depressive disorder. Case Report. Here, we present the case of a 49-year-old man diagnosed with major depressive disorder, severe, with psychotic features, who was treated with antidepressants and underwent multiple antipsychotic trials. The patient was found to have low serum levels of vitamin D. During treatment with vitamin D, serum levels normalized and the patient’s psychotic symptoms abated. Conclusion. Ensuring adequate vitamin D levels could be a method of focus for the augmentation or treatment of psychotic features in major depressive disorder.